2015
DOI: 10.1586/14760584.2015.1060859
|View full text |Cite
|
Sign up to set email alerts
|

Review of invasive meningococcal disease during the last 40 years in Turkey

Abstract: Due to the lack of comprehensive surveillance data representing Turkey, the authors aimed to derive information by panoramically reviewing all articles related to invasive meningococcal disease (IMD) published in the last 40 years. The following databases were reviewed: Ulakbim (the national database), BIOSIS Previews (from 1995), Evidence-Based Medicine Reviews-Cochrane Database of Systematic Reviews (from 2005), Embase (from 1996), Ovid MEDLINE(R) (from 1946) and Journals@Ovid Full Text (2014). Twenty-seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
1
2
0
2
Order By: Relevance
“…28 A review of studies in Turkey shows that they are usually performed in a single region and include a limited number of participants, finding a carriage rate ranging from 1.2% to 28%. 12 Bakir et al 29 isolated N. meningitidis in 17 out of 1382 asymptomatic children aged 0-10 y and found a carriage rate of 1.23%; the most prevalent serogroup was Y, and there was no presence of serogroup C, similar to our study. The present study included adolescents and young adults from 12 provinces of Turkey and found a carriage rate of 6.3%, which is the most representative of the country so far.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…28 A review of studies in Turkey shows that they are usually performed in a single region and include a limited number of participants, finding a carriage rate ranging from 1.2% to 28%. 12 Bakir et al 29 isolated N. meningitidis in 17 out of 1382 asymptomatic children aged 0-10 y and found a carriage rate of 1.23%; the most prevalent serogroup was Y, and there was no presence of serogroup C, similar to our study. The present study included adolescents and young adults from 12 provinces of Turkey and found a carriage rate of 6.3%, which is the most representative of the country so far.…”
Section: Discussionsupporting
confidence: 90%
“…10 It can be explained by the Hajj pilgrimage, which is among the effective risk factors associated with carriage in Turkey. In a study of specimens collected before and after the Hajj, Ceyhan et al 37 showed that the prevalence of carriage was 13% before and reached 27% after pilgrimage; 91% of the specimens were positive for serogroup W. In a review of 27 reports on invasive meningococcal infections over the past 40 y in Turkey, Bakir et al 12 found that the serogroup W was not common during the 1970s but became the most common invasive pathogen over time. Although serogroup W does not seem to be the most common cause in Turkish studies on carriage, we found that it was the most frequent cause, with a rate of 66.6%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mevcut konjuge aşıların [Haemophilus influenzae tip B (Hib), Streptococcus pneumoniae ve N.meningitidis] kullanımı ile bakteriyel menenjitin etyolojik sebepleri büyük ölçüde değişmiştir 3,4 . Hib ve S.pneumoniae'ya karşı konjuge aşılar Ulusal Aşı Takvimimize girdikten sonra Hib kaynaklı menenjit olgusu 2012 yılından itibaren görülmemekte, S.pneumoniae kaynaklı menenjit olgusu ise oldukça azalmış olup, N.meningitidis önde gelen etken olarak karşımıza çıkmaktadır.…”
Section: Olgu Sunumuunclassified
“…2005 yılından önce Türkiye'de invaziv meningokokal hastalık için epidemiyolojik çalışma ve takip yapılmamış olup, serogruplar belirlenmemiştir. Yapılmaya başlayan sürveyans ile hastalık yapan serogrupların yıllar içinde değişkenlik gösterdiği görülmektedir 3 . Bu çalışmada, son yıllarda ülkemizde nadir görülen serogrup C ve serogrup Y meningokoksemisi görülen iki olgu sunulmuştur.…”
Section: Introductionunclassified